ANALISIS RANCANGAN TEKNOLOGI MOBILE APPLICATION PADA E-BOOKING RUANGAN UNTUK KEGIATAN UKM - Agus Purwanto; Anggun Nugroho (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTStudents Activity Unit or abbreviated UKM in STIKOM Bali is a student organization managed bystudents under the coordination of Assistant III Chairman of Student Affairs. Activities undertakenby SMEs is a non-academic activities that are useful to mediate interests and talents of students inthe field of non-academic. Currently more than 25 SMEs in STIKOM Bali are coordinated by PKIII. Activities undertaken are usually done on campus and off campus by utilizing the space andfascities available on campus itself. To use the existing room and facilities SME managers mustplace orders to the relevant sections so that their use can be controlled. Room reservation systemis done so far still using the manual way that SME managers come directly to units of Facilitiesand Infrastructure (SARPRAS) to reserve the space to be used. Therefore, it is necessary to applyfor room rental booking with Android based for SME managers easier to book the room. but alsoto facilitate SME managers to obtain information on the available space at the desired time. Withthe application of this application later lending space can be resolved by using information andcommunication technology (ICT), without having to come directly to the unit Sarpras so that therelevant part easier to manage and monitor the use of the room by SMEs in STIKOM Bali. Thismobile app is built using android operating system using Android Studio. This application allowscustomers to register and make room reservations in accordance with the time required and thetype of room in accordance with the capacity of the room. This application also uses My SQL fordatabase storage as well as using the application adobe dreamweaver to create a web server to beeasily dikelaola by the administrator in this Sarpras unit.Keywords : ukm, booking, booking system, androidABSTRAKUnit Kegiatan Mahaiswa atau disingkat UKM di STIKOM Bali merupakan organisasi mahasiswayang dikelola oleh mahasiswa dibawah koordinasi Pembantu Ketua III Bidang Kemahasiswaan.Kegiatan yang dilakukan oleh UKM ini adalah kegiatan non akademis yang berguna untukmemediasi minat dan bakat para mahasiswa di bidang non akademis. Saat ini lebih dari 25 UKMdi STIKOM Bali yang dikoordinasi oleh PK III. Kegiatan-kegiatan yang dilakukan biasanyadilakukan di kampus dan di luar kampus dengan memanfaatkan ruangn dan fasislitas yang tersediadi kampus itu sendiri. Untuk menggunakan ruangan dan fasilitas yang ada para pengurus UKMharus melakukan pemesanan ke bagian terkait agar penggunaannya dapat terkontrol. Sistempemesanan ruangan yang dilakukan selama ini masih menggunakan cara manual yaitu pengurusUKM datang langsung ke unit Sarana dan Prasarana (SARPRAS) untuk memesan ruang yangakan digunakan. Oleh karena itu, diperlukan aplikasi pemesanan peminjaman ruangan denganberbasis Android agar pengurus UKM lebih mudah untuk memesan ruangan. selain itu juga untukmemudahkan pengurus UKM memperoleh informasi ruangan yang tersedia pada waktu yangdiinginkan. Aplikasi mobile ini dibangun dengan menggunakan sistem operasi android denganmenggunakan Android Studio. Aplikasi ini memungkinkan pelanggan melakukan registrasi danmelakukan pemesanan ruangan sesuai dengan waktu yang dibutuhkan serta jenis ruangan sesuaidengan kapasitas ruangan. Aplikasi ini juga menggunakan My SQL untuk penyimpanan basis dataserta menggunakan aplikasi adobe dreamweaver untuk membuat web server agar dapat mudahdikelaola oleh administrator dalam hal ini unit Sarpras.Kata kunci : ukm,pemesanan, sistem booking, android